The Effects of Corrosive Media on Fatigue Performance of Structural Aluminum Alloys - Huihui Yang; Yanling Wang; Xishu Wang; Pan Pan; Dawei Jia (Metals, 2016)
The effects of corrosive media on rotating bending fatigue lives (the cyclic numbers from 104 to 108) of different aluminum alloys were investigated, which involved the corrosion fatigue lives of five kinds of aluminum alloys in air, at 3.5 wt. % and 5.0 wt. % NaCl aqueous solutions. Experimental results indicate that corrosive media have different harmful influences on fatigue lives of different aluminum alloys, in which the differences of corrosion fatigue lives depend strongly on the plastic property (such as the elongation parameter) of aluminum alloys and whether to exist with and without fracture mode II. The other various influence factors (such as the dropping corrosive liquid rate, the loading style, and the nondimensionalization of strength) of corrosion fatigue lives in three media were also discussed in detail by using the typical cases. Furthermore, fracture morphologies and characteristics of samples, which showed the different fatigue cracking behaviors of aluminum alloys in three media, were investigated by scanning electron microscopy (SEM) in this paper.